Characterization of New Recombinant Forms of HIV-1 From the Comunitat Valenciana (Spain) by Phylogenetic Incongruence - Beamud, Beatriz; Bracho, María Alma; González-Candelas, Fernando (Frontiers in Microbiology, 2019)
Recombination is one of the main processes shaping the evolution of HIV-1, with relevant consequences for its epidemiology and, possibly, the efficacy of treatments. Up to date, more than 80 circulating recombinant forms (CRFs) have been described which add to the 9 “pure” subtypes recognized for the M group of this virus. The characterization of recombination events and variants can be very laborious, especially in light of the increasing amount of partially or completely sequenced viral samples. Besides, there is no standard methodological procedure for describing and accepting new recombination events. Here, we implement a slightly modified protocol to sequence nearly whole genome sequences of HIV-1 from sera and a pipeline to detect (by means of jpHMM or RDP4) and, independently, contrast recombination events. The latter is based in phylogenetic topology congruence testing, which shows improved reliability over other methods for subtype assignment. We have applied this method to describe 9 new recombinant forms from the Comunitat Valenciana, Spain. We found two samples related to CRF44_BF whereas the rest correspond to new URFs. Some of these reveal a complex recombination pattern that may have arisen by successive recombination events among diverse lineages.